LEO or LEO baby within enterprise overlapping stents combined with coil embolization treatment for ruptured vertebrobasilar artery dissecting aneurysms - Zengbao Wu; Minghui Zhou; Ali Abdi Maalim; Yang Han; Xiao Guo; Cao Chen; Ting Lei; Kai Shu; Mingxin Zhu (Scientific Reports)
Abstract This study sought to evaluate the feasibility and effectiveness of the LEO or LEO baby within enterprise (EP) overlapping stents for treating ruptured vertebrobasilar artery dissecting aneurysms (VBDAs). A retrospective analysis was conducted on 20 patients with a total of 20 ruptured VBDAs, who received reconstructive treatment utilizing the LEO/LEO baby within enterprise overlapping stents combined with coil embolization, between December 2018 and June 2023. Patient characteristics, clinical outcomes, and radiological results were thoroughly reviewed. Functional data were evaluated using the modified Rankin scale (mRS). The outcomes for patients treated with the overlapping stent technique were compared to those of the single-stent treatment group which included 14 cases with LEO/LEO Baby stent and 12 cases with Enterprise stent. Among the 20 ruptured VBDAs identified, 13 were vertebral artery aneurysms (65.00%), and 7 were basilar artery aneurysms (35.00%). All cases were effectively treated during the acute phase of onset. Three patients (15.00%) experienced significant in-hospital adverse events, with one patient (5.00%) succumbing to rebleeding of the arterial aneurysm during the perioperative period. A follow-up period of at least six months was achieved for 19 patients. The rates of mortality or dependency (mRS scores of 3 to 6) were 15.00% at discharge and 10.00% at the final follow-up. Ischemic events occurred in two patients (10.00%); one during the perioperative period and one during follow-up. One patient (5.00%) required ventriculoperitoneal shunt placement. Immediate post-operation angiography revealed Raymond grade I, II, and III occlusions in 55.00%, 30.00%, and 15.00% of cases, respectively. At a mean follow-up of 14.84 ± 7.51 months, 17 patients (89.47%) had mRS scores of 0–2, indicating favorable outcomes, while two patients (10.53%) had scores between 3 and 6. The initial complete or near-complete obliteration rates of aneurysms were higher in the overlapping-stent group compared to the single-stent group (85.00% vs. 65.38%, P = 0.18). Follow-up angiography indicated superior rates of complete or near-complete aneurysm obliteration in the double-stent group (94.74% vs. 73.08%, P = 0.11). The overlapping stents technique, utilizing the LEO/LEO baby within EP stent configuration in conjunction with coiling, demonstrated both efficacy and safety in the treatment of ruptured VBDAs. Follow-up evaluations revealed a high rate of aneurysm occlusion, suggesting that this approach may offer a dependable intervention strategy for managing these complex cases.